1988
DOI: 10.1111/j.1365-3024.1988.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis: the non‐specific binding of different species of immunoglobulins to alveolar hydatid cysts grown in vivo and in vitro

Abstract: Alveolar hydatid cysts (AHC) were isolated from C57BL/6J and BALB/c mice at 8 and 12 weeks post-infection from subcutaneous and intraperitoneal foci and cultured in vitro. Freshly isolated as well as in vitro-grown cysts were incubated with Fc or F(ab')2 fragments of human, rabbit, mouse, goat or sheep immunoglobulins, then washed and incubated with a fluorescein-conjugated rabbit or goat F(ab')2 fraction of antisera to each of the above primary sera. Significant fluorescence on the surface of AHC was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The morphology of metacetodes generated in vitro as well as in vivo (separated from the host in a micropore chamber; Nahhas et al 1991) was very similar to that of metacestodes isolated from the peritoneum of experimentally infected mice and gerbils (Delabre et al 1987;Mehlhorn et al 1983). The parasite tissue was surrounded by the acellular laminated layer, a structure that is known to play a decisive role in protecting the parasite from its host's immune reaction (Alkarmi et al 1988;Gottstein et al 1992Gottstein et al , 1994. That this laminated layer was always present during cultivation in vitro clearly indicated that this structure was synthesized by the parasite itself.…”
Section: Discussionmentioning
confidence: 90%
“…The morphology of metacetodes generated in vitro as well as in vivo (separated from the host in a micropore chamber; Nahhas et al 1991) was very similar to that of metacestodes isolated from the peritoneum of experimentally infected mice and gerbils (Delabre et al 1987;Mehlhorn et al 1983). The parasite tissue was surrounded by the acellular laminated layer, a structure that is known to play a decisive role in protecting the parasite from its host's immune reaction (Alkarmi et al 1988;Gottstein et al 1992Gottstein et al , 1994. That this laminated layer was always present during cultivation in vitro clearly indicated that this structure was synthesized by the parasite itself.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of immunoglobulins on parasite surfaces has been well documented (see Alkarmi et al (1988) for references). For example, immunoglobulins of the IgG 2 b class were found attached to, and in the integument of adult Schistosoma mansoni and tetrathyridia of Mesocestoides corti (Sogandares-Bernal, 1976;Sogandares-Bernal & Voge, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the tegumental surface of adults and metacestodes, limited to a restricted number of species, has generally revealed a complex array of macromolecules, some of which exhibit enzyme activity, with molecular weights ranging from < 10000 to > 200000 (Knowles & Oaks, 1979;McManus & Barrett, 1985;McManus et al 1987;Parkhouse & Harrison, 1987). Components of host origin, including immunoglobulins and serum albumin, have also been identified on the surfaces of several species (Befus, 1977;Craig, 1988;Shepherd & McManus, 1987;Alkarmi, Alshakarchi & Behbehani, 1988;Smyth & McManus, 1989). In addition, a number of surface-associated proteins have been found on the oncosphere stage (Harrison & Parkhouse, 1986; see Craig, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…1981), the cestodes Taenia solium (Flisser, Espinoza, Tovar et al . 1986), Taenia crassiceps (Kalinna & McManus 1993) and Taenia taeniaeformis (Kwa & Liew 1978), as well as within the genus Echinococcus on E. multilocularis (Alkarmi, Alshakarchi & Behbehani 1988). The results obtained in all those cases suggest that the immunoglobulins are adsorbed on the parasite surface through interactions with Fc‐receptors (Kemp et al .…”
Section: Introductionmentioning
confidence: 99%